In Vitro Activity of Auranofin in Combination With Aztreonam-Avibactam Against Metallo-β-lactamase (MBL)-Producing Enterobacterales - Wang, Wen; Huang, Shifeng; Zou, Chunhong; Ding, Yanhui; Wang, Huijuan; Pu, Shuli; Liao, Yunfeng; Du, Hong; Wang, Deqiang; Chen, Liang; Niu, Siqiang (Frontiers in Cellular and Infection Microbiology, 2021)
Objectives: To assess the efficacy of aztreonam-avibactam-auranofin (ATM-AVI-AUR) against a collection of 88 carbapenemase-producing Enterobacterales (CPE) clinical isolates and 6 in vitro selected ATM-AVI-resistant CPE with CMY-16 Tyr150Ser and Asn346His mutants or transformants. Methods: MICs of imipenem, ceftazidime-avibactam (CAZ-AVI), ATM-AVI, CAZ-AVI-AUR and ATM-AVI-AUR were determined via the broth microdilution method. Genetic background and carbapenemase genes were determined by PCR and Sanger sequencing. Results: AUR alone showed little antibacterial activity (MIC50/90>64/>64 μg/mL) when the AUR MICs were greater than 64 μg/mL for all the 88 clinical CPE isolates. The addition of AUR (16 μg/mL) resulted in an 8-fold reduction of ATM-AVI MIC50 (0.5 to 0.0625 μg/mL) and a 4-fold reduction of MIC90 (1 to 0.25 μg/mL) against all 88 clinical CPE isolates, respectively. Notably, the reduced ATM-AVI MIC values were mainly found in MBL-producers, and the MIC50 and MIC90 reduced by 4 folds (0.25 to 0.0625 μg/mL) and 8 folds (2 to 0.25 μg/mL) respectively by AUR among the 51 MBL-producers. By contrast, the addition of AUR did not showed significant effects of ATM-AVI MIC50 (0.0625 μg/mL) and MIC90 (0.125 μg/mL) among single KPC-producers. Interestingly, the addition of AUR re-sensitized the ATM-AVI susceptibility against the 6 in vitro selected ATM-AVI-resistant CMY-16 Tyr150Ser and Asn346His mutants or transfromants, with the MICs reduced from ≥32 μg/mL (32->256 μg/mL) to ≤8 μg/mL (0.0625-8 μg/mL). Conclusions: Our results demonstrated that AUR potentiated the activities of CAZ-AVI and ATM-AVI against MBL-producing isolates in vitro. Importantly, AUR restored the ATM-AVI activity against ATM-AVI resistant mutant strains. As a clinical approved drug, AUR might be repurposed in combination with ATM-AVI to treat infections caused by highly resistant MBL-producing Enterobacterales.